Acute diarrhoea in a community cohort of children who received an oral rotavirus vaccine in Northeast Brazil - Sarah Cristina Fontes Vieira (Memórias do Instituto Oswaldo Cruz., 2011)
Rotavirus is an important cause of childhood diarrhoea. A monovalent rotavirus vaccine (Rotarix®) was introduced into the Immunization Program of Brazil in 2006. In this study, we describe the incidence and burden of disease of rotavirus diarrhoea in two cohorts of children (vaccinated and unvaccinated). We followed two groups of 250 children under one year old, who were enrolled in December 2006 from a low-income residential area in Northeast Brazil. The children were monitored every two weeks for two years. Stool samples from children with diarrhoea were examined for the presence of rotavirus. Rotaviruses were genotyped using real time-polymerase chain reaction. The mean numbers of all-cause diarrhoea episodes/child (adjusted for age) in the first year were 0.87 and 0.84, in vaccinated and unvaccinated children, respectively. During the second year, the number of episodes/child decreased to 0.52 and 0.42. Only 16 (4.9%) of 330 stool samples were rotavirus-positive (10 vaccinated and 6 unvaccinated children) and only P[4]G2 rotaviruses were identified. All-cause diarrhoea episodes were more severe in unvaccinated children in the first year of age (p < 0.05), while vaccinated children had more severe episodes 18 months after vaccination. Rotavirus diarrhoea incidence was very low in both groups.